Global Use of Idarucizumab in Clinical Practice: Outcomes of the RE-VECTO Surveillance Program - Fanikos, John; Murwin, Debra; Gruenenfelder, Fredrik; Tartakovsky, Igor; França, Lionel Riou; Reilly, Paul A.; Kermer, Pawel; Wowern, Fredrik von; Lane, Deirdre A.; Butcher, Ken (Thrombosis and Haemostasis, 2020)
Idarucizumab was approved for the reversal of dabigatran in 2015. We investigated whether postapproval usage patterns of idarucizumab in a real-world setting reflect those observed in the pivotal trials. No safety or efficacy data were collected in this medical record-based observational study. RE-VECTO, a global postapproval, international, surveillance program, involved hospital pharmacies in countries where idarucizumab was licensed and dispensed (August 2016–June 2018). Characteristics of sites prescribing idarucizumab and of eligible patients (≥ 18 years old and receiving idarucizumab regardless of prior oral anticoagulant use), as well as idarucizumab utilization data, were collected and analyzed descriptively. Sixty-one sites enrolled 359 patients. Most pharmacies (85.2%) were centralized, and the median idarucizumab units stocked per hospital was 2.0 (interquartile range, 1.0–3.0). Almost three-quarters of patients were elderly (74.9% aged > 70 years), and only four (1.1%) had received idarucizumab before. Nearly all patients were treated with dabigatran (97.5%). There was a low frequency of unapproved dabigatran dosage regimens (3.3%). Life-threatening or uncontrolled bleeding was the most frequent indication for idarucizumab (57.7%), followed by emergency surgery/urgent procedure (35.9%). Of the life-threatening bleeding events, the most frequent were gastrointestinal tract (44.4%) and intracranial (38.6%). Most patients (95.0%) were given the full dose of two vials (2 × 2.5 g) of idarucizumab initially, and very few (1.7%) received a second dose. Of those patients requiring emergency or scheduled/planned surgery/procedures, 25.5% underwent gastrointestinal and/or abdominal surgery/procedures. Real-world usage patterns of idarucizumab provide valuable insights into emergency reversal strategies. Off-label use was minimal.
Keywords: anticoagulation; idarucizumab; dabigatran etexilate; real-world utilization; reversal agent